Christianity and the law of migration - Allard, Silas W.; Heyer, Kristin E., 1974-; Nadella, Raj (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This collection brings together legal scholars and Christian theologians for an interdisciplinary conversation responding to the challenges of global migration. Gathering fourteen leading scholars from both law and Christian theology, the book covers legal perspectives, theological perspectives, and key concepts in migration studies. In part one, scholars of migration law and policy discuss the legal landscape of migration at both the domestic and international level. In part two, Christian theologians, ethicists, and biblical scholars draw on the resources of the Christian tradition to think about migration. In part three, a scholar of law and a scholar of Christian theology bring their respective resources and perspectives into conversation through a co-authored chapter on key themes within migration studies. The work provides a truly interdisciplinary introduction to the topic of migration for those who are new to the subject; an opportunity for immigration lawyers and legal scholars to engage Christian theology; an opportunity for pastors and Christian theologians to engage law; and new insights on key frameworks for scholars who are already committed to the study of migration"--
Introduction : law and theology in the age of migration / Silas W. Allard -- Exclusion, admission, and deportation : categorical evolution and normative challenges / Daniel Kanstroom -- The institutionalization of inequality : lower-skilled and undocumented workers in immigration law / Enid Trucios-Haynes -- In defense of chain migration / Bill Ong Hing -- The state of the law on refugees, asylees, and stateless persons / Michele R. Pistone -- Borders : sites of exclusion, sites of engagement / Silas W. Allard -- Immigrant integration and disintegration in an era of exclusionary nationalism / Donald M. Kerwin Jr. -- True faith, allegiance, and citizenship / Rose Cuison Villazor -- Different kinds of foreignness : the Hebrew Bible's terminology for foreigners / Safwat Marzouk -- Embrace, ambivalence, and theoxenia : new testament perspectives on hospitality to strangers / Raj Nadella -- Toward a theology of migration / Luis N. Rivera-Pagán -- When the poor knock on our door : a theological response to unwanted migration / Gemma Tulud Cruz -- The theopolitics of the migrant : toward a coalitional and comparative political theology / Ulrich Schmiedel -- Migration, social responsibility, and moral imagination : resources from Christian ethics / Kristin E. Heyer -- "No more deaths" : religious liberty as a defense for providing sanctuary for immigrants / Rose Cuison Villazor and Ulrich Schmiedel -- A vision of integration rooted in hospitality / Donald M. Kerwin Jr.and Safwat Marzouk -- Labor, inequality, and globalization : legal and theological perspectives on vulnerable migrant workers / Gemma Tulud Cruzand Enid Trucios-Haynes -- Empire, displacement, and the Central American refugee crisis / Bill Ong Hingand Raj Nadella -- Empathy, legitimacy, faith, and the dangerously uncertain future of migration / Kristin E. Heyerand Daniel Kanstroom.
Keywords: Emigration and immigration law -- United States; United States -- Emigration and immigration -- Religious aspects -- Christianity; LAW / General; LAW / Administrative Law & Regulatory Practice; LAW / Civil Rights